2008
DOI: 10.1016/j.bbrc.2008.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of the DFNA5 increases risk of lymph node metastasis in human breast cancer

Abstract: The pathogenesis of breast cancer involves multiple genetic and epigenetic events. In this study, we report an epigenetic alteration of DFNA5 in human breast cancer. DFNA5 gene was silenced in breast cancer cell lines that were methylated in the DFNA5 promoter, and restored by treatment with the demethylating agent, 5-aza-dC, and gene knock-down of DFNA5 increased cellular invasiveness in vitro. The mRNA expression of DFNA5 in breast cancer tissues was downregulated as compared to normal tissues. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
127
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 15 publications
(24 reference statements)
13
127
5
1
Order By: Relevance
“…In breast carcinoma, the methylation status of DFNA5 was correlated with lymph node metastasis. 15 These recent data also explain earlier findings that were not well understood at the time, such as the increased resistance to the chemotherapeutic reagent etoposide in melanoma cells with decreased transcription of DFNA5, 11 or the finding that DFNA5 is induced by p53 through a p53-binding site located in intron 1. 12 Webb et al 17 demonstrated that DFNA5 mRNA expression increased after treatment of human acute lymphoblastic leukemia cell lines with the glucocorticoid dexamethasone.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…In breast carcinoma, the methylation status of DFNA5 was correlated with lymph node metastasis. 15 These recent data also explain earlier findings that were not well understood at the time, such as the increased resistance to the chemotherapeutic reagent etoposide in melanoma cells with decreased transcription of DFNA5, 11 or the finding that DFNA5 is induced by p53 through a p53-binding site located in intron 1. 12 Webb et al 17 demonstrated that DFNA5 mRNA expression increased after treatment of human acute lymphoblastic leukemia cell lines with the glucocorticoid dexamethasone.…”
Section: Introductionsupporting
confidence: 68%
“…Methylation of the 5Âą-flanking region of DFNA5, as frequently observed in gastric, colorectal and breast carcinoma, [13][14][15][16] may be a way to prevent the apoptotic actions of DFNA5. We believe that our description of the apoptosis-inducing mechanism of DFNA5 contributes to the growing evidence that DFNA5 may be a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…85,86 Cancer-specifi c methylation is, however, a rather rare event, and is presumably only recognized in the genes with robust tumor suppressive function. [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] Methylation of CpG islands for normal genes occurs at random, but hypomethylation is more common in cancer cells than in normal tissues. 104,105 As a result, gene promoter methylation that is related to cancer development or progression is relatively rare, and it is worth further investigation to determine whether these methylated genes can be used as candidate biomarkers and therapeutic targets.…”
Section: Epigenetic Alterations In Gastric Cancermentioning
confidence: 99%